Influence of Parents’ Educational and Socio-Economic Status on Dental Health of Children Among South Indian Population - SURESH, NILESH; KUMAR M, NAVEEN (The journal of contemporary issues in business and government, 2021)
In the modern era where both parents are employed, there seems to be limited focus on the dietary habits and dental health of their children. Hence, the aim of this study was to assess the parental influence and family characteristics on the prevalence of dental caries among children who reported to the department of Orthodontics aged 10-17 years from Chennai. A cross-sectional epidemiological survey was carried out on 250 children aged 10 years to 17 years. The data was retrieved from the subjects records provided by the institution which consisted of information on their dental caries status. Structured questionnaires were given to parents to collect information regarding their socio-environmental and family characteristics. Student's t-test on metric parameters and Chi-square/Fisher for study parameters between two or more groups were used. It was observed that in families where the average monthly income >10,000/-, decayed, missing, and filled teeth was proportionately lower. The socioeconomic status, which is primarily influenced by parental factors and family structure, have a definite role in dental needs of children from underprivileged backgrounds. Dental health programs should aim to reduce the gross inequalities in the oral health status of these children and their families.